Leaf Epidermal Studies of the Species of Emilia Cass. (Senecioneae, Asteraceae) in Nigeria - Adedeji, Olubukola (2014)
A taxonomic study of Emilia Cass. in Nigeria was conducted in search of useful and stable anatomical characters for the identification of the species. Stomatal type and index indicates that Emilia praetermissa is a hybrid between E. coccinea and E. sonchifolia. Larger cell size in all studied size attributes supports E. praetermissa as an allotetraploit. Trichome type, stomata type, stomata shape and size attributes are all characters of E.sonchifolia and E. praetermissa that were consistently close in resemblance and values to suggest E. sonchifolia as the closer parent of E. praetermissa exerting gene dominance. This would also suggest introgression between E. sonchifolia and E. praetermissa.